The impact of adding hp-hMG in r-FSH started GnRH antagonist cycles on ART outcome. (3rd October 2019) - Kan, Ozgur; Simsir, Coskun; Atabekoglu, Cem Somer; Sonmezer, Murat
Abstract: While luteinizing hormone (LH) activity is believed to play a role in follicle maturation, human chorionic gonadotropin (hCG) might play an important role in implantation process. We aimed to investigate whether addition of human menopausal gonadotropin (hMG) in recombinant-follicle-stimulating hormone (r-FSH) started GnRH antagonist controlled ovarian hyperstimulation (COH) cycles might enhance implantation rate and improve in vitro fertilization (IVF) success. A total of 246 patients undergoing GnRH antagonist IVF cycles were analyzed. One hundred and twenty-three cycles (%50) were treated with only r-FSH and 123 cycles were treated with r-FSH plus hp-hMG combination. Total gonadotropin doses, total number of oocytes retrieved, metaphase 2 (MII) oocytes, top quality embryos, fertilization and implantation rates, clinical pregnancy rates (CPRs) and ovarian hyperstimulation syndrome (OHSS) rates were compared between the groups. Both groups were comparable in terms of demographic details and baseline characteristics. Peak estradiol and progesterone levels in hCG trigger day, number of retrieved oocytes and top quality embryo counts, fertilization rates were similar between the groups. In r-FSH + hp-hMG group, significantly higher implantation rates (35.3% vs 24.3%, p =.017), CPRs (51.2% vs 35.8%, p =.015) and lower OHSS rates (1.6% vs 7.4%, p = .03) were observed respectively compared to r-FSH only treated patients. In conclusion, addition of hp-hMG on the day of antagonist initiation might increase CPRs. A better endometrial receptivity associated with higher implantation rates might be achieved due to hCG component in hp-hMG.